Prevalence, distribution, enterotoxin profiles, antimicrobial resistance, and genetic diversity of Bacillus cereus group isolates from lettuce farms in Korea - Rajalingam, Nagendran; Jung, Jieun; Seo, Seung-Mi; Jin, Hyun-Sook; Kim, Bo-Eun; Jeong, Myeong-In; Kim, Dawoon; Ryu, Jae-Gee; Ryu, Kyoung-Yul; Oh, Kwang Kyo (Frontiers in Microbiology, 2022)
Lettuce wraps are popular in Korean cuisine for their high nutritional value and versatility as healthy additions to multiple dishes. Microbial contamination of lettuce is a major concern, as lettuce is consumed fresh without cooking. Among foodborne pathogens, the spore-forming, facultative anaerobic bacterium, Bacillus cereus is one of the frequently detected pathogen in lettuce in Korea. In this study, we investigated the prevalence and distribution of Bacillus cereus strains in lettuce production farms and further evaluated the enterotoxin gene profiles, antibiotic susceptibility, multidrug resistance pattern, and genetic differences among the B. cereus group isolates. Of the 140 samples isolated from 10 lettuce production farms, 30 samples (21.42%) were positive for B. cereus in which 19 (31.6%) and 10 (23.25%) were from soil and lettuce, respectively. The enterotoxin patterns A (hblCDA, nheABC, entFM, and cytK genes) and B (hblCDA, nheABC, and entFM genes) accounted for 50% and 20% of all the isolates, whereas the emetic gene cesB was not detected in any of the B. cereus group isolates. Antibiotic susceptibility testing of the B. cereus group isolates revealed that all the strains were predominantly resistant to β-lactam antibiotics except imipenem and generally susceptible to most of the non β-lactam antibiotics, including gentamycin, streptomycin, chloramphenicol, and tetracycline. ERIC-PCR and MLST analysis revealed high genetic diversity among the 30 B. cereus group isolates, which belonged to 26 different sequence types (STs) and seven new STs. Moreover, isolates with identical STs exhibited similar patterns of antibiotic resistance and enterotoxin profiles. Results of this study indicate a high prevalence of B. cereus group isolates in lettuce production farms in the Republic of Korea.